"Gregaria" to "Subrugosa, " that is the Question: Shape Changes Under Laboratory Conditions in the Pelagic Morphotype of the Squat Lobster Munida Gregaria () (Decapoda: Anomura: Munididae). Issue 4 (1st July 2016) - Diez, Mariano J.; Rojas-Quiroga, María Laura; Pérez-Barros, Patricia; Lezcano, Aníbal; Florentín, Olga; Lovrich, Gustavo A.
Abstract: Munida gregaria (Fabricius, 1793 ) is one of the few species of squat lobsters (Anomura, Munididae) with two morphotypes, one with a post-metamorphic pelagic phase that eventually settles to the bottom ("gregaria") and a second that is exclusively benthic ("subrugosa"). This study provides the first information on the growth of the pelagic morphotype of M. gregaria and its relation with changes in morphology in southern South America. Specifically, we studied growth at molt and duration of the intermolt period in the laboratory and analyzed changes in morphology through growth by means of geometric morphometry techniques. Fifty squat lobsters were sampled from shoals in the Beagle Channel, Tierra del Fuego and kept in individual flasks during 29 months. The carapace of each exuvia was photographed and analyzed using 2D geometric morphometry analysis. Changes in shape associated with growth in the gregaria morphotype were gradual, adjusted to a linear function, and occurred mainly in the anterior portion of the carapace. After two years and at least eight molts, however, individuals of the gregaria morphotype were still clearly distinguishable from a typical individual of the subrugosa morphotype. These results suggests that once sexual maturity is attained, pelagic individuals of M. gregaria do not transform from gregaria to subrugosa, and retain the gregaria morphology.